(untitled) (European Journal of Pure and Applied Mathematics, 2010)
This paper is concerned with initial value problem of the nonlinear coupled Â Schrodinger equations. We study local well posedness in the Banach algebra E^0_2,1(R^n) which is the extension of H^s(R^n) when Â sn2. The method we use is similar to the method of semigroup.